Technologiczne aspekty ryzyka operacyjnego w bankach - Garczyński, Dariusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The development of IT technology enables implementation of new tools thatallow a bank to build competitive advantage. However, new technologies alsocause increase of the risk level that is associated with them, which is part of theoperational risk in the bank. Key trends in the development of electronic societynot only generate potential profits for the banks but are a source of new threatsthat need to be analyzed in order to avoid potentially serious problems in thebanking sector.